2020
DOI: 10.3389/feduc.2019.00152
|View full text |Cite
|
Sign up to set email alerts
|

Open Educational Resources as a Tool for Educational Equity: Evidence From an Introductory Psychology Class

Abstract: A college education is becoming increasingly expensive, and the burden of this cost is often felt disproportionately by marginalized students. One aspect of rising college costs are textbook prices, which have increased at a rate that far surpasses inflation. Open educational resources (OER; free, openly-licensed course materials) are often proposed as a solution to this problem. It is not clear, however, whether these materials are equivalent in quality to standard commercial textbooks. During one semester, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 19 publications
4
35
0
1
Order By: Relevance
“…Latinx and first-generation students also were more likely to report that they failed a course because of the high cost of the textbook (Jenkins et al, 2019). In addition, students who identified as both first generation college students and of Black or Latinx background were more likely than their white peers to report that high textbook costs led to lower grades (Nusbaum et al, 2019).…”
Section: Oer Cost-savings and Educational Access And Successmentioning
confidence: 98%
See 1 more Smart Citation
“…Latinx and first-generation students also were more likely to report that they failed a course because of the high cost of the textbook (Jenkins et al, 2019). In addition, students who identified as both first generation college students and of Black or Latinx background were more likely than their white peers to report that high textbook costs led to lower grades (Nusbaum et al, 2019).…”
Section: Oer Cost-savings and Educational Access And Successmentioning
confidence: 98%
“…When students withdraw from courses after the drop deadline, they are still responsible for the tuition for that course. The issue of commercial material costs contributing to course withdrawals appears to be particularly problematic for first-generation college students (Nusbaum et al, 2019).…”
Section: Oer Cost-savings and Educational Access And Successmentioning
confidence: 99%
“…Wiley (2014) elaborates that OER must provide users with the permissions to reuse, revise, remix, redistribute, and retain those resources. Several studies have suggested that the use of OER is associated with similar or better student outcomes as compared to the use of commercial course materials (Clinton & Khan, 2019;Colvard et al, 2018;Delgado et al, 2019;Jhangiani et al, 2018;Lin & Wang, 2018;Nusbaum et al, 2020;Shaw et al, 2019). OER are often framed in the context of educational affordability but using an OER textbook as a direct replacement for a commercial textbook, while beneficial to students in terms of cost savings, fails to take full advantage of the entire range of permissions described by Wiley and others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…on RStudio's shinyapps.io platform), which dramatically reduces the need for computational power on students' personal computers or mobile devices. Unlike some other proprietary simulation platforms that charge substantial fees, shiny apps can be made freely available to students, making them more equitable classroom materials (Colvard et al 2018, Nusbaum et al 2020. Further, shiny apps are straightforward to build for users with some R proficiency, which makes it easy for instructors to develop new apps or to customize existing resources to suit their classroom needs.…”
Section: Introductionmentioning
confidence: 99%